Community-acquired pneumonia as medical emergency: predictors of early deterioration. Issue 6 (17th March 2015) - Kolditz, Martin; Ewig, Santiago; Klapdor, Benjamin; Schütte, Hartwig; Winning, Johannes; Rupp, Jan; Suttorp, Norbert; Welte, Tobias; Rohde, Gernot
Abstract : Background: Early organ dysfunction determines the prognosis of community-acquired pneumonia (CAP), and recognition of CAP as a medical emergency has been advocated. Objective: To characterise patients with 'emergency CAP' and evaluate predictors for very early organ failure or death. Methods: 3427 prospectively enrolled patients of the CAPNETZ cohort were included. Emergency CAP was defined as requirement for mechanical ventilation or vasopressor support (MV/VS) or death within 72 h and 7 days after hospital admission, respectively. To determine independent predictors, multivariate Cox regression was employed. The ATS/IDSA 2007 minor criteria were evaluated for prediction of emergency CAP in patients without immediate need of MV/VS. Results: 140 (4%) and 173 (5%) patients presented with emergency CAP within 3 and 7 days, respectively. Hospital mortality of patients presenting without immediate need of MV/VS was highest. Independent predictors of emergency CAP were the presence of focal chest signs, home oxygen therapy, multilobar infiltrates, altered mental status and altered vital signs (hypotension, raised respiratory or heart rate, hypothermia). The ATS/IDSA 2007 minor criteria showed a high sensitivity and negative predictive value, whereas the positive predictive value was low. Reduction to 6 minor criteria did not alter accuracy. Conclusions: Emergency CAP is a rare but prognostic relevant condition, mortality is highest in patients presenting without immediate need of MV/VS. Vital sign abnormalities and parameters indicating acute organ dysfunction are independent predictors, and the ATS/IDSA 2007 minor criteria show a high negative predictive value.